Canon/Archive studies in quantitative formalism from the Stanford Literary Lab - Moretti, Franco (Brooklyn, NY : n+1 Foundation, 2017)
For the past seven years, the Stanford Literary Lab, founded by Franco Moretti and Matthew Jockers, has been a leading site of literary scholarship aided by computers and algorithmic methods. This landmark volume gathers the collective research of the group and its most remarkable experiments. From seemingly ineffable matters such as the "loudness" of thousands of novels, the geographic distribution of emotions, the nature of a sentence and a paragraph, and the evolution of bureaucratic doublespeak, descriptions emerge. The Stanford Literary Lab lets the computers provide new insights for questions from the deep tradition of two centuries of literary inquiry. Rather than, like the rest of us, letting the computers lead. The results are adventurous, witty, challenging, profound. The old questions can finally get new answers--as the prelude to new big questions. Canon/Archive is the fulfillment and further development of "distant reading," adding a rare, full-length monument to the piecemeal progress of the digital humanities. No student, teacher, or inquisitive reader of literature will want to be without this book--just as no one interested in the new data-attentive methods in history, criticism, and the social sciences can afford to evade its summons
Literaturverz. S. 309 - 315 "The chapters in this book were originally published as pamphlets by the Stanford Literary Lab" (Rückseite des Titelblatts)
Keywords: Literaturwissenschaft; Digital Humanities; Aufsatzsammlung